Analysis through Implementation of Government Accounting Standards on Accrual Base - Sagala, Syarah Asda Pratiwi; Marliyah, Marliyah; Nurwani, Nurwani (Journal of Business Management and Economic Development, 2024)
This research aims to determine the application of accrual-based Government Accounting Standards in the presentation of financial reports at the North Labuhanbatu Regency Central Statistics Agency and to determine the suitability of the presentation of the North Labuhanbatu Regency Central Statistics Agency's financial reports with Government Regulation Number 71 of 2010. This research method uses qualitative methods with interviews and documentation. The subjects of this research are employees of the accounting and finance department at BPS Kab. North Labuhanbatu. The results of the first research: Application of Government Accounting Standards in the Presentation of Financial Reports of the North Labuhanbatu Regency Central Statistics Agency refers to Government Regulation Number 71 of 2010, BPS Labura Financial Reports have been prepared and presented on an accrual basis, but accrual basis accounting is still not fully implemented because it still exists. the financial report component that uses the cash basis is the Budget Realization Report. The results of the second research state that the presentation of the financial reports of the North Labuhanbatu Regency Central Statistics Agency is not 100% in accordance with Government Regulation Number 71 of 2010. This is because there are still several posts that are not implemented, namely transfer posts and financing posts in the Budget Realization Report